Myoclonus in Patients With Coronavirus Disease 2019: A Multicenter Case Series. Issue 11 (November 2020) - Anand, Pria; Zakaria, Asma; Benameur, Karima; Ong, Charlene; Putman, Maryann; O'Shea, Sarah; Greer, David; Cervantes-Arslanian, Anna M.
Abstract : Objectives: To describe the risk factors for and outcomes after myoclonus in a cohort of patients with coronavirus disease 2019. Design: Multicenter case series. Setting: Three tertiary care hospitals in Massachusetts, Georgia, and Virginia. Patients: Eight patients with clinical myoclonus in the setting of coronavirus disease 2019. Interventions & Measurements and Main Results: Outcomes in patients with myoclonus were variable, with one patient who died during the study period and five who were successfully extubated cognitively intact and without focal neurologic deficits. In five cases, the myoclonus completely resolved within 2 days of onset, while in three cases, it persisted for 10 days or longer. Seven patients experienced significant metabolic derangements, hypoxemia, or exposure to sedating medications that may have contributed to the development of myoclonus. One patient presented with encephalopathy and developed prolonged myoclonus in the absence of clear systemic provoking factors. Conclusions: Our findings suggest that myoclonus may be observed in severe acute respiratory syndrome coronavirus 2 infected patients, even in the absence of hypoxia. This association warrants further evaluation in larger cohorts to determine whether the presence of myoclonus may aid in the assessment of disease severity, neurologic involvement, or prognostication. Abstract : Supplemental Digital Content is available in the text.